1992
DOI: 10.1002/pc.750130207
|View full text |Cite
|
Sign up to set email alerts
|

The influence of processing on fiber orientation and creep in short carbon‐fiber reinforced low density polyethylene and polycarbonate

Abstract: This paper is concerned with the creep behavior of short fiber‐reinforced thermoplastics, especially with regard to the role of fiber orientation. Rectangular samples of low density polyethylene (LDPE) and polycarbonate (PC) containing varying amounts of carbon fibers were prepared by compression and injection molding. The materials were compounded using a technique producing a concentration independent fiber length distribution. The orientation distribution, on the other hand, was found to be strongly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…An extensive research effort has been conducted to evaluate fiber breakage during processing. A number of techniques have been developed for investigating fiber length degradation in compounded and molded materials [5,6,9,11,14,19,23,24,28,29,32,55,56]. In all the techniques employed, fibers must be separated from the polymer matrix.…”
Section: Fiber Length Distribution (Fld)mentioning
confidence: 99%
See 3 more Smart Citations
“…An extensive research effort has been conducted to evaluate fiber breakage during processing. A number of techniques have been developed for investigating fiber length degradation in compounded and molded materials [5,6,9,11,14,19,23,24,28,29,32,55,56]. In all the techniques employed, fibers must be separated from the polymer matrix.…”
Section: Fiber Length Distribution (Fld)mentioning
confidence: 99%
“…In all the techniques employed, fibers must be separated from the polymer matrix. The polymer matrix may be removed by burning off in an oven [5,6,9,11,19,23,28,29,55,56] or by dissolving the polymer in an appropriate solvent [14,24,32]. It has been shown that fiber breakage in processing of reinforced thermoplastics results from fiberpolymer interaction, fiber-fiber interaction, and fiber contact with surfaces of processing equipments [24].…”
Section: Fiber Length Distribution (Fld)mentioning
confidence: 99%
See 2 more Smart Citations
“…By increasing the fiber fraction, the material response magnitude increases (i.e., increase in relaxation modulus or decrease in creep compliance), and material time-dependency decreases (decrease in relaxation or creep rate), since the fibers may be obstructing the polymer's molecular mobility [7][8][9][10][11]. It's important to mention i.)…”
Section: Introductionmentioning
confidence: 99%